2017
DOI: 10.1039/c6ra27824h
|View full text |Cite
|
Sign up to set email alerts
|

Bio-oil production via catalytic solvolysis of biomass

Abstract: Recent studies have found that biomass has great potential as a substitute for natural fossil fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 44 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Figure 2 c shows the influence of liquefaction temperature and time on the liquefaction yield of CS. It can be seen that the high temperature had a positive effect on the liquefaction yield, revealing the thermal domination in the liquefaction reaction [ 13 ]. When the temperature was ≤140 °C, the glycosidic linkages in the CS decomposed into smaller soluble fragments with the reaction of dehydration and decarbonylation under the catalysis of sulfuric acid [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 c shows the influence of liquefaction temperature and time on the liquefaction yield of CS. It can be seen that the high temperature had a positive effect on the liquefaction yield, revealing the thermal domination in the liquefaction reaction [ 13 ]. When the temperature was ≤140 °C, the glycosidic linkages in the CS decomposed into smaller soluble fragments with the reaction of dehydration and decarbonylation under the catalysis of sulfuric acid [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the high temperature (250–400 °C) and high pressure (5–40 MPa) are usually required for the solvent to reach a supercritical state during the direct liquefaction process [ 11 ], which would limit its application in the practical production [ 12 ]. Compared to direct liquefaction, solvolysis liquefaction, with the merits of low reaction pressure (1 atm) and temperature (100–200 °C), is a more preferable method, which can convert lignocellulosic biomass into valuable intermediates under relatively mild reaction conditions [ 13 , 14 , 15 ]. Moreover, the selection of solvents for the solvolysis liquefaction is very important to prevent liquefied products from cross-linking and repolymerizing [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major References Method of bio-oil conversion [32][33][34][35][36][37][38][39][40][41] Chemical compound analysis [42][43][44][45] Optimization of process design and parameters [46][47][48][49][50][51][52][53][54][55][56] Upgrading of bio-oil [57,58] Energy and environment [30,[59][60][61][62][63][64][65][66][67][68] 2. Conversion of Oil Palm EFB to Bio-Oil: Principles and Processes…”
Section: Categorymentioning
confidence: 99%
“…Table 3 The first category comprises papers on the methodology of biomass conversion into bio-oil [32][33][34][35][36][37][38][39][40][41]. It covers the pyrolysis and liquefaction process in producing bio-oil.…”
Section: Oil Palm Efb Characterization and Compound Analysismentioning
confidence: 99%
“…[25] and some other researchers [26,27] also found the temperature is an efficient parameter for both the experiments with and without a catalyst for the hydrothermal-fluidization process. Duo and Aminul et al [28] have found that HT bio-oil yield can be increased at lower temperatures by using oil palm fronds as raw material and ZnO/ZSM-5 as a catalyst (Figure 2). The authors believe the isomerization reaction of sugar in lignocellulose components occurs at low temperatures, and bio-oil is mainly composed of acetaldehyde.…”
Section: Introductionmentioning
confidence: 99%